Islamic Education Educators during the Abbasid Dynasty (Analysis of Historical Studies of Islamic Education) - Sapii, Muhammad (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to find out the names of educators during the Abbasid Dynasty and to find out who the caliphs were during. The historical method consists of data collection, source criticism, interpretation and finally historiography. The research approaches used in this research are a geographic approach, a sociological approach, an educational approach and historical education. The results of this research are that the educators presented by the researchers were 14 people, namely: 1) Imam Abu Hanifah Rahimahullah (80-150 H/700-767 M), 2) Imam Malik Rahimahullah (93 -179 H/712-796 M), 3) Imam Syafi’i Rahimahullah (150-204 H/767-820 M), 4) Imam Ahmad Rahimahullah (164-241 H/781-856 M), 5) Imam Ad-Darimi Rahimahullah (181-255 H/798-869 M), 6) Imam Al-Bukhari Rahimahullah (194-256 H/810-871 M), 7) Imam At-Tarmidzi Rahimahullah (200-279 H/816-892 M), 8) Imam Abu Daud Rahimahullah (202-275 H/818-889 M), 9) Imam Muslim Rahimahullah (204-261 H/820-875 M), 10) Imam Ibnu Majah Rahimahullah (209-273 H/825-887 M), 11) Imam An-Nasaai Rahimahullah (215-303 H/830-906 M), 12) Abu Ja’far Muhammad bin Jarir Ath-Thabari Rahimahullah (224-310 H/839-923 M), 13) Imam Daarud Ad-Qudni Rahimahullah (306-385 H/919-995 M), dan 14) Imam Al-Baihaqi Rahimahullah (384-458 H/995-1.066 M).